Sex differences in the outcomes of modifiable lifestyle factors for cognitive aging: neuroinflammation and microglia as key underlying mechanisms - Samantha G. Coleborn; Samantha G. Coleborn; Zoë M. Gilson; Zoë M. Gilson; Yunyong Guo; Yunyong Guo; Marie-Ève Tremblay; Marie-Ève Tremblay (Frontiers in Aging Neuroscience, 2025)
Microglia are the resident immune cells of the brain. Over the past two decades, they have been shown to play critical roles throughout life. Microglia are now considered to be important for brain formation, maturation, activity and plasticity, with outcomes on behavior and other cognitive domains. With this knowledge, microglia represent a promising therapeutic target to promote brain health along an aging trajectory. Emerging evidence also indicates that modifiable lifestyle factors for cognitive aging can influence the brain and behavior by acting on microglia. The mechanisms identified so far involve their roles in synaptic plasticity, axonal myelination, and adult neurogenesis, exerted through the modulation of brain inflammation (‘neuroinflammation’), the release of trophic factors, and phagocytosis. In this mini-review, we will cover the outcomes of exercise, diet. and social isolation on microglial functions during aging. Sex differences in the identified outcomes on cognitive aging and the underlying mechanisms will be highlighted. Our goal with this mini-review is to stimulate further research on this important topic.